2021
DOI: 10.3390/cancers13081844
|View full text |Cite
|
Sign up to set email alerts
|

Video-Laparoscopic versus Open Surgery in Obese Patients with Colorectal Cancer: A Propensity Score Matching Study

Abstract: Background: Minimally invasive surgery in obese patients is still challenging, so exploring one more item in this research field ranks among the main goals of this research. We aimed to compare short-term postoperative outcomes of open and video-laparoscopic (VL) approaches in CRC obese patients undergoing colorectal resection. Methods: We performed a retrospective analysis of a surgical database including 138 patients diagnosed with CRC, undergoing VL (n = 87, 63%) and open (n = 51, 37%) colorectal surgery. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…In a previous case-matched study conducted at our institution [ 7 ], we found that VL surgery correlates with better short-term outcomes, in terms of the degree of complication (one point less according to Clavien-Dindo, on average) and length of stay (almost two days shorter). In contrast, we found that fewer harvested lymph nodes were found for the VL group.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In a previous case-matched study conducted at our institution [ 7 ], we found that VL surgery correlates with better short-term outcomes, in terms of the degree of complication (one point less according to Clavien-Dindo, on average) and length of stay (almost two days shorter). In contrast, we found that fewer harvested lymph nodes were found for the VL group.…”
Section: Discussionmentioning
confidence: 70%
“…Postoperative hospitalization time differed significantly between the two groups, either before or after matching, with fewer days for subjects allocated to VL surgery, and the Clavien-Dindo post-operative severity classification system showed no differences across surgery groups. Anyhow, the short-term results of the same sample have been already discussed elsewhere [ 7 ]. Lastly, the observation time, i.e., follow-up, proved to be significantly longer for subjects undergoing VL surgery, predicting better long-term outcomes ( p < 0.01).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Due to the popularity of laparoscopic surgery and the development of surgical equipment such as electrothermal bipolar activation devices and ultrasound systems, the average intraoperative blood loss (IBL) has decreased ( 6 , 7 ). However, IBL is still a matter of concern during the operation.…”
Section: Introductionmentioning
confidence: 99%